Komunikasi Antar Umat Beragama di Kota Ambon - Hakis, Hakis (Jurnal Komunikasi Islam, 2015)
Communication is essential in our lives, including communication for inter-religious harmony. The beauty of the peaceful life, post-communal conflict in Ambon city is a dream of the whole society. Through interviews with some Muslim and Christian religious leaders, this article argues that in order to establish harmony in Ambon, it would require the following steps (1) to stop the language of incitement; (2) communicate to always refrain; (3) to communicate with the language of peace, from bottom to top and vice versa; (4) engage in dialogue, open networking among adolescents, and multicultural education; (5) public space as a meeting space for the socio-cultural level must be consi–dered; (6) the management of peace itself.